Ambientes de aprendizaje para el desarrollo de destrezas con criterio de desempeño en el Área de Entorno Natural y Social, con los estudiantes de tercer año de Educación Básica de la unidad educativa “Once de Noviembre” en el cantón Riobamba, provincia de Chimborazo periodo 2015 – 2016. - Morocho Lema, María Magdalena (2016)
The present research was carried out to structure learning environments for the development of skills with criteria of performance in the area of natural and social environment, in the students of third year of Basic Education of the Educational Unit “11 de Noviembre”. A theoretical basis was made based on variables such as Learning environments and Skills with performance criteria, to find the proposed objective, first it was determined which are the skills with performance criterion required for teaching Of the Natural and Social environment, secondly an analysis was made of the conditions in which the learning environments are found through a survey carried out with the teachers, regarding the level of development of the skills with criterion of performance was realized An initial evaluation, observing the skills that the children possessed in the different activities carried out related to the curricular planning related to the elaboration of small classroom projects, considering as a factor to evaluate the indicators of achievement, contents and methodology for meaningful learning, with The results obtained and considering the deficiencies in terms of learning environments that affect the classrooms and the Education Unit, it was proposed to carry out activities through the methodology of projects and the contents of the level, which by their characteristics allowed to improve the learning environments of Temporal form and made possible the collaborative work. In the process of executing the project activities students were evaluated, data were collected with checklists, knowledge achievements were revealed in the development of children`s performance criteria and Girls. The results obtained allowed to establish differences between the initial evaluation and the observations made during the intervention, from the results obtained it was possible to conclude that the planning for the area and the level handles an interesting number of skills with performance criteria, however there are no Conditions of adequate learning environments, so that the application of the project methodology based on the curricular contents for its evaluation contributes to the development of these capacities, recommending this methodology to overcome the failures of the environments.